Chaotic evolutionary-based image encryption using RNA codons and amino acid truth table. (December 2020) - Abbasi, Ali Asghar; Mazinani, Mahdi; Hosseini, Rahil
Highlight: Hidden key with SHA-256 algorithm is intended for the initial value of hyper chaos. Using of the two bit level permutation technique and the hyper chaos function. RNA and amino acid codons are intended for the diffusion of image pixels. Using evolutionary algorithm to increase entropy and reduce correlation coefficient. Using the operators of the imperialist competition algorithm for pixels diffusion. Abstract: With the increasing use of Internet and mass media, information security has become an important issue in the field of communication. Image encryption is one of the ways to secure information in communications. In this paper, a Chaotic Evolutionary Amino Acid Codons Model (CEAACM) is presented for image encryption. The proposed model consists of four phases. In the first phase, a hidden key is provided using the SHA-256 algorithm for the initial value of the hyper chaos function. In the second phase, the permutation and diffusion of image pixels are done using two bit level permutation and Hyper Chaos Function. In the next phase, RNA and amino acid codons are used for the diffusion operation, and in the fourth phase, the process performed in the previous phases is repeated by the initial population number of the imperialist competition algorithm. Then in the next step, the optimization is performed using the operators of the imperialist competition algorithm. The results show the superiority of the proposed model over other models. In addition, according to the high value of entropy, the proposed model is highly resistant to common attacks.